Pengaruh Penggunaan Mobile Banking Bri Terhadap Continuance Intention Pada Generasi Z - Antika Sari; Nikmah Nikmah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Mobile banking is a bank payment transaction service that allows customers to carry out various transactions using smartphones. This research aims to examine the relationship between variables in predicting the intention to continue using BRI mobile banking in generation Z. The variables in this study are continuous intention, satisfaction, calculative commitment, affective commitment, trust, perceived service value, alternative quality, and anxiety. This research method uses quantitative methods, and data collection techniques in this research were carried out using questionnaires and purposive sampling design. The number of respondents was 198 respondents with generation Z research objects. Before the data was analyzed for hypothesis testing, the data was first tested for reliability and validity to ensure that the measures measured were good. Then, the data was analyzed for hypothesis testing using PLS structural equation modeling (SEM). The results of this analysis show that all hypotheses can be supported or are significant. This research also conveys limitations and suggestions for further research. Keywords: Intention To Continue Using, SEM, BRI Mobile Banking, Generation Z